Disaster and Development Examining Global Issues and Cases - Kapucu, Naim; Liou, Kuotsai Tom (Environmental Hazards, 2014)
This book offers a systematic, empirical examination of the concepts of disasters and sustainable economic development applied to many cases around the world. It presents comprehensive coverage of the complex and dynamic relationship between disaster and development, making a vital contribution to the literature on disaster management, disaster resilience, and sustainable development. The book collects twenty-three chapters, examining theoretical issues and investigating practical cases on policy, governance, and lessons learned in dealing with different types of disasters (e.g., earthquakes, floods, and hurricanes) in twenty countries and communities around the world.